International social entrepreneurship pathways to personal and corporate impact - Muñoz, J. Mark S. (International business collection, 2010)
Social entrepreneurship, or the business practice with the dual bottom line of profit and service, has steadily increased worldwide. While high profile success cases are notable, business failures are mounting. This book introduces the concept of "international social entrepreneurship" and outlines contemporary challenges and opportunities. Based on real life cases and internationalization theories, it offers practical instructions for readers to strategically replicate social ventures from one part of the world to another. With the confluence of business globalization and civic-mindedness, an entrepreneurial wave is bound to change the world through its personal and corporate impact.